Numerical Simulation and Comparison Study of the Atmospheric Intraseasonal Oscillation - 李崇银 凌健 贾小龙 董敏 (Acta meteorologica Sinica, 2007)
Daily mean outputs for 12 yr （1978-1989） from two general circulation models （SAMIL-R42L9 and CAM2.0.2） are analyzed and compared with the corresponding NCEP/NCAR reanalysis dataset, and results in two models show clearly that the root-mean square errors （RMSEs） from the simulation of intraseasonal oscillation can take 30-40 percent of the total RMSE, particularly, the distributions of the RMSE in simulating intraseasonal oscillation are almost identical with that of the total RMSE. The maximum RMSE of intraseasonal oscillation height at 500 hPa is shown in the middle latitude regions, but there are also large RMSEs of intraseasonal oscillation wind over the tropical western Pacific and tropical Indian Oceans. The simulated ISO energy in the tropic has very large difference from the result of the NCEP/NCAR reanalysis dataset which means the simulation of tropical atmospheric ISO still possesses serious insufficiency. Therefore, intraseasonal oscillation in the weather and climate numerical simulation is very important, and thus, how to improve the ability of the GCM to simulate the intraseasonal oscillation becomes very significant.